2023
DOI: 10.1177/13506501231177485
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of journal bearing having surface waviness operating under misaligned condition

Arun Bangotra,
Sanjay Sharma,
Reza Taufique
et al.

Abstract: In this present study, the effect of surface waviness on the performance of journal bearing operating in misaligned conditions has been investigated. The journal’s misaligned conditions in the present analysis are taken about the circumferential, the axial, and both axes. For computing the pressure of lubricant inside the bearing, the finite element method has been applied to solve the Reynolds equation and thus static parameters are obtained. The static parameters, that is, load carrying capacity and coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Jamali et al [24,25] showed that the bearing performance can be improved by using a variable bearing profile. More recently, the misalignment problem in journal bearing has also been investigated by [26][27][28]. However, all these works did not consider the effect of changing the geometrical bearing profile parameters on the system response to unbalance excitations.…”
Section: Introductionmentioning
confidence: 99%
“…Jamali et al [24,25] showed that the bearing performance can be improved by using a variable bearing profile. More recently, the misalignment problem in journal bearing has also been investigated by [26][27][28]. However, all these works did not consider the effect of changing the geometrical bearing profile parameters on the system response to unbalance excitations.…”
Section: Introductionmentioning
confidence: 99%